Obesity as a risk factor for COVID‐19 mortality in women and men in the UK biobank: Comparisons with influenza/pneumonia and coronary heart disease. Issue 1 (11th October 2020) - Peters, Sanne A. E.; MacMahon, Stephen; Woodward, Mark
Abstract: Obesity is associated with severe COVID‐19 outcomes, yet, it is unclear whether the risk of COVID‐19 mortality associated with obesity is similar between the sexes. We used data from the UK Biobank to assess the risk of COVID‐19 mortality associated with various anthropometric measures in women and men. To put these results in context, we also compared these estimates with those for mortality from influenza/pneumonia and coronary heart disease (CHD). The analyses included 502 493 individuals (54% women), of whom 410 (36% women) died from COVID‐19, 549 (36% women) died from influenza/pneumonia and 3355 (19% women) died from CHD. A higher body mass index (BMI), waist circumference, waist‐to‐hip ratio and waist‐to‐height ratio were each associated with a greater risk of death from COVID‐19, influenza/pneumonia and CHD in both sexes, with the exception of the association between higher BMI and the risk of influenza/pneumonia death in men. A higher BMI was associated with a stronger risk of COVID‐19 mortality in women than men; the women‐to‐men ratio of hazard ratios was 1.20 (95% confidence interval 1.00; 1.43). This study demonstrates the role of obesity in COVID‐19 mortality and shows that the relative effects of a higher BMI on COVID‐19 mortality may be stronger in women than men.